An efficient and sustainable synthesis of NHC gold complexes. Issue 62 (12th July 2016) - Johnson, Alice; Gimeno, M. Concepción
Abstract : A simple, efficient and sustainable method for the general synthesis of NHC gold(i ) complexes is described. Abstract : A simple, efficient and sustainable method for the general synthesis of NHC gold(i ) complexes is described. The reaction of imidazolium salts, of different electronic and steric requirements, with [AuX(tht)] (tht = tetrahydrothiophene) derivatives, in the presence of NBu4 (acac), in air and at room temperature leads to the NHC gold species in good yields and with very short reaction times.